Choroidal vascularity index as an activity criterion and a treatment response measure in chronic central serous chorioretinopathy - ŞAHİN, ÖZLEM; SEVİK, MEHMET ORKUN; ÇAM, FURKAN; DERİCİOĞLU, VOLKAN (My University, 2023)
Purpose: This study aimed to evaluate the choroidal vascularity index (CVI) as an activity criterion in chronic central serous chorioretinopathy (CSC) and as a measure of treatment response after full-dose-full-fluence photodynamic therapy (fd-ff-PDT). Methods: This fellow-eye-controlled, retrospective cohort study included 23 patients with unilateral chronic CSC treated with fd-ff-PDT (6 mg/m2; 50 μcm2; 83 s). Subfoveal choroidal thickness (SFCT, μm) and CVI (%) of the affected and fellow eyes at baseline as well as at 1, 3 and 6 months after fd-ff-PDT were compared. Results: The patients\" mean age was 43.4 ± 7.3 years, and 18 (78.3%) were male. CVI was comparable between the affected and fellow eyes at baseline (66.09 ± 1.56 vs. 65.84 ± 1.57, p = 0.59). However, it became significantly lower in the affected eyes 1 (64.45 ± 1.68 vs. 65.87 ± 1.19, p = 0.002), 3 (64.21 ± 2.08 vs. 65.71 ± 1.59, p = 0.009) and 6 (64.47 ± 2.19 vs. 65.62 ± 1.52, p = 0.045) months after fd-ff-PDT. The mean SFCT and the mean CVI were significantly decreased in the affected eyes at all follow-up visits compared with baseline after fd-ff-PDT (p < 0.001). Conclusion: At baseline, CVI was comparable between affected and fellow eyes. Therefore, its use as an activity criterion in chronic CSC patients is questionable. However, it was significantly decreased in fd-ff-PDT-treated eyes, supporting its role as a measure of treatment response in chronic CSC.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Sinirbilim ve Davranış; GÖZ HASTALIKLARI; SİNİR BİLİMİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; NEUROSCIENCE & BEHAVIOR; OPHTHALMOLOGY; NEUROSCIENCES; Oftalmoloji; Optometri; Duyusal Sistemler; Ophthalmology; Optometry; Sensory Systems; central serous chorioretinopathy; choroidal vascularity index; subfoveal choroidal thickness